Evaluation of Minimum Service Standard Implementation in Surakarta City in 2020-2022 - Ardianti, Faradila Putri; Satyanovi, Vidia Ayu; Ardila, Lina Nur (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This study aims to examine the development of the Minimum Service Standards (SPM) budget in Surakarta City from 2020 to 2022 and evaluate the implementation of SPM according to the principles set out in Government Regulation Number 2 of 2018. The research employs a descriptive qualitative approach, utilizing data collection methods such as interviews, observations, literature review, and documentation. The results of this study reveal that the SPM budget in Surakarta City fluctuated between 2020 and 2022, with increases due to the COVID-19 pandemic and subsequent decreases as the pandemic's impact lessened. Surakarta City has complied with all the SPM principles outlined in Government Regulation Number 2 of 2018. This study recommends that the Surakarta City Financial and Asset Management Agency (BPKAD) continue prioritizing the SPM budget. Moreover, it is advised that BPKAD ensure that relevant regional authorities adhere to SPM principles effectively.